2010
DOI: 10.1007/s10646-010-0498-8
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of coal-tar pavement sealants and ultraviolet radiation to Ambystoma Maculatum

Abstract: Polycyclic aromatic hydrocarbons (PAHs) can affect amphibians in lethal and many sublethal ways. There are many natural and anthropogenic sources of PAHs in aquatic environments. One potentially significant source is run off from surfaces of parking lots and roads that are protected with coal tar sealants. Coal tar is 50% or more PAH by wet weight and is used in emulsions to treat these surfaces. Break down of sealants can result in contamination of nearby waters. The toxicity of PAHs can be greatly altered by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…This result extends previous reports of toxicity in similar samples (Bommarito et al, 2010a; Bommarito et al, 2010b; McQueen et al, 2010) to another organism, and to a life stage that is frequently particularly vulnerable to toxicant exposure (Lanphear et al, 2005; McKim, 1977; Rand et al, 1995). …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This result extends previous reports of toxicity in similar samples (Bommarito et al, 2010a; Bommarito et al, 2010b; McQueen et al, 2010) to another organism, and to a life stage that is frequently particularly vulnerable to toxicant exposure (Lanphear et al, 2005; McKim, 1977; Rand et al, 1995). …”
Section: Discussionsupporting
confidence: 89%
“…However, PLRRP have no filtering or treatment features and routinely contain complex mixtures of metals, salts, PAHs, heterocyclic aromatic compounds and other organic constituents (Bartlett et al, 2012; Gobel et al, 2007; McQueen et al, 2010; Wium-Andersen et al, 2011). This impaired water quality is of concern as contaminated PLRRPs routinely overflow, sending constituents into the surrounding ecosystems (Mahler et al, 2012; Wilson, 2011), and exposure to PLRRP samples causes toxicity in several aquatic species (Bommarito et al, 2010a; Bommarito et al, 2010b; McQueen et al, 2010). This source of pollution may be especially relevant in coast areas, which contain sensitive marine species.…”
Section: Introductionmentioning
confidence: 99%
“…37 Salamanders ( Ambystoma maculatum ) and newts ( Notophthalmus viridescens ) exposed to sediment contaminated with coal-tar-based sealcoat at PAH concentrations similar to the highest treatment in the frog study had stunted growth, difficulty swimming or righting themselves, and liver problems. 38,39 These effects were magnified by the addition of UV light. 38 At the community level, macroinvertebrate communities exposed to sediment spiked with coal-tar-based sealcoat had significant decreases in species abundance and richness at ΣPAH 16 concentrations exceeding 300 mg/kg.…”
Section: Introductionmentioning
confidence: 99%
“…38,39 These effects were magnified by the addition of UV light. 38 At the community level, macroinvertebrate communities exposed to sediment spiked with coal-tar-based sealcoat had significant decreases in species abundance and richness at ΣPAH 16 concentrations exceeding 300 mg/kg. 40 Similarly, in a study of urban streams, aquatic invertebrate communities downstream from parking lots with coal-tar-based sealcoat suffered losses of abundance and diversity along a gradient of increasing total PAH concentration, starting near the ΣPAH 12 probable effects concentration (PEC) value of 22.8 mg/kg.…”
Section: Introductionmentioning
confidence: 99%
“…One field‐based study examined the abundance of aquatic organisms upstream and downstream of RCTS‐sealed parking lots (Scoggins et al ). Some studies examined phototoxic effects of UV radiation (UVR) (Bommarito et al ; Kienzler et al ; Mahler et al ), which has been shown to interact with PAHs and increase photo‐enhanced toxicity (Diamond et al ). Some studies compared the biological effects of RCTS with those of conventional asphalt‐based pavement sealer (Bommarito et al ; Titaley et al ), but the toxicity of asphalt‐based sealers is not the focus of this review.…”
Section: Resultsmentioning
confidence: 99%